2010
DOI: 10.1016/j.pepi.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity of (K,Na)AlSi3O8 hollandite from lattice dynamics calculations

Abstract: We compute the elastic constants tensor and the seismic properties of KAlSi 3 O 8 and K 0.8 Na 0.2 AlSi 3 O 8 up to the ferroelastic transition using density-functional theory and density-functional perturbation theory in the ABINIT implementation. We observe a softening of the tetragonal shear with pressure that precedes the ferroelastic transition. The Reuss shear moduli become negative at respectively 23 GPa and 13 GPa for the two compositions considered in here. The ferroelastic transition is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
(20 reference statements)
1
21
0
Order By: Relevance
“…The derivatives can also be calculated using density functional perturbation theory (Hamann et al, 2005), but the use of ultrasoft pseudopotentials make the implementation of this approach particularly challenging. Examples of the use of this method for Earth materials are comparatively sparse, but include Bagigan (2009) andBoffa Ballaran (2010). A common alternative approach is used here.…”
Section: Methodsmentioning
confidence: 99%
“…The derivatives can also be calculated using density functional perturbation theory (Hamann et al, 2005), but the use of ultrasoft pseudopotentials make the implementation of this approach particularly challenging. Examples of the use of this method for Earth materials are comparatively sparse, but include Bagigan (2009) andBoffa Ballaran (2010). A common alternative approach is used here.…”
Section: Methodsmentioning
confidence: 99%
“…With the set of six elastic stiffness coefficients, standard formulas for the bulk (B) and shear (G) moduli for the tetragonal Laue group TI in the Voigt [57], Reuss [58], and Hill [59] approximations, labeled with subscripts V , R, and H , respectively, can be then applied [60]:…”
Section: B Elastic Propertiesmentioning
confidence: 99%
“…Ab initio simulation has unparalleled advantages in exploring information associated with unquenchable high-pressure phase transitions, and this technique has been widely applied to phase transitions of different types (e.g., Waghmare and Rabe 1997;Meng et al 2004;Iitaka et al 2004;Martinez and Durandurdua 2006;Durandurdua 2009aDurandurdua , 2009b. For the composition KAlSi 3 O 8 , three theoretical calculations have been carried out so far (Winkler et al 2002;Mookherjee and Steinle-Neumann 2009a;Caracas and Boffa Ballaran 2010). Winkler et al (2002) mainly developed a new method to investigate the Al/Si disorder in silicates and briefly reported their simulated Holl-I structure at zero pressure only.…”
Section: Introductionmentioning
confidence: 99%
“…To the contrary, Mookherjee and Steinle-Neumann (2009a) carried out a detailed investigation for a large range of pressure on the elasticity and phase stability of Holl-I and Holl-II. The third study aimed at the elasticity and seismic property of Holl-I (Caracas and Boffa Ballaran 2010). On the other hand, some theoretical calculations have also been made to explore the effect of Na (Boffa Ballaran et al 2009;Caracas and Boffa Ballaran 2010) that suggested the replacement of K by Na decreases the phase-transition pressure between Holl-I and Holl-II.…”
Section: Introductionmentioning
confidence: 99%